Asphalt material characterization, accelerated testing, and construction management : selected papers from the 2009 GeoHunan International Conference, August 3-6, 2009, Changsha, Hunan, China - Walubita, Lubinda F. (Geotechnical special publication ;, 2009)
"This Geotechnical Special Publication contains 25 papers presented at the GeoHunan International Conference: Challenges and Recent Advances in Pavement Technologies and Transportation Geotechnics, which took place in Changsha, Hunan, China from August 3 to 6, 2009. This proceedings showcases recent developments and advancements in geotechnical and pavement engineering, and offers insights into future directions for geoengineering in the 21st century." "The topics examined in this collection illuminate the breakthroughs and underscore the challenges in geotechnical and pavement engineering, especially with regard to highways, and include: Asphalt Binder and Mixture Characterization; Recycled Asphalt Materials and Pavements; Accelerated Testing of Pavement Structures and Materials; Economy and Management of Highway Engineering; and Embankment Stabilization and Tunnelling."